(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article deals with the theoretical and methodological principles of the study of character’s accentuations. It describes the specific of psychological development in the youth. The article presets the results of the empirical research of the features of character’s accentuations in adolescence. It is revealed which types of accentuations prevail in the representatives of this age category and how they appear in the young people’s behavior. Сertain types of character’s accentuations were identified among 72% of respondents. Hyperthymic, cyclothymic, emotive types of accentuation expressed more often. Anxious, unbalanced and dysthymic types were not determined among the students. These types can significantly affect the development of deviant behavior and social disadaptation of the individual.